OPERATIONS PRE-CONTINUOUS MAPPINGS IN TOPOLOGICAL SPACES - Saravanakumar, D.; Kalaivani, N.; Krishnan, G. Sai Sundara (Acta Scientiae et Intellectus, 2024)
In this paper, we define the operations mappings in topological spaces such as -pre-continuous, pre-open, -pre-closed, -pre-closed and -pre-homeomorphism and study some their basic properties.